Urban Development and Industrial Clustering in Pakistan: A Study Based on Geographical Perspective - Khalida Mahmood; Razzaq Ahmed; Nighat Bilgrami-Jafferi (Journal of Basic & Applied Sciences, 2016)
The urban clusters serve as powerful magnets of economic opportunities and facilities for a large number of population. The only space they are able to grab are shanty town which are either very closely located or adjacent to major industrial zones in large cities of the world including Pakistan. Certainly these industrial estates capture the labor markets located nearby. These shanty towns have emerged as a result of in-migrant influx from the interior of the country and provinces. The clusters are geographical and sector wise concentration of numerous producers and ancillary agents, engaged in production, supply or trade activities. These are directly associated with the manufacturing of a specific product or set of products hence clusters constitute the core of industrial districts. An industrial district can now be defined as a geographical and spatial concentration of firms whose organization of products is marked by a dense network of local inter-firm relations. In order to investigate the urban development and geo-spatial agglomeration in Pakistan PCA has been run using eleven variables representing urban industrial infrastructure. The results reveal the significant role played by large industrial clusters contained in various urban centers of the country. This role is well reflected in the population potential of each of these urban centers.